(Trans)formations of the clown: Brief history of classic types of clowning art (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article updates results on the research (Trans)formations of the clown: History of Types and Techniques of Clowning Art (2014). This research aimed to understand the constitution of the clown character. Through various references. main classic types were presented, the comic duo White clown and Auguste, and the Contra-Auguste, while identifying some of their characteristics. Itis supposed that the diversity found in different contexts has influenced the ways the clown is conceived today. This contribution makes thus possible to reflect on the cultural development of clowning art.
Keywords: Performing arts; Circus arts; Clowning art; Clown; Comic types